Light-Emitting Diode Therapy in Chemotherapy-Induced Mucositis - Sacono, Nancy T. [UNESP]; Costa, Carlos A. S. [UNESP]; Bagnato, Vanderlei S.; Abreu e Lima, Fabio Cesar Braga de [UNESP] (Wiley-liss, 2008)
Background and Objective: Mucositis is the most common oral complication of cancer chemotherapy, which causes pain on mastication and swallowing, impairs patients' ability to eat and take oral drugs and may determine interruption of the treatment. The aim of this study was to evaluate the effect of light-emitting diode (LED) therapy on chemotherapy-induced mucositis in hamsters.Study Design/Materials and Methods: Animals of both experimental (Group 1; n = 32) and positive control (Group II; n = 32) groups received intraperitoneal injections of 5-fluorouracil on days 0 and 2. All animals had their right and left cheek pouch irritated by superficial scratching on days 3 and 4. In Group I, LED irradiation (630 nm +/- 10 nm, 160 mW, 12 J/cm(2)) was applied during 37.5 seconds at days 3, 4, 6, 8, 10, 12, and 14. In Group II, mucositis was induced, but LED therapy was not performed. The oral mucosa was photographed from day 4 to 14 at 2-day intervals. Photographs were randomly scored according to the severity of induced mucositis (0 to 5). In the negative control group (Group III; n = 6), no mucositis was induced. Biopsies of the cheek pouches of 8 animals (Group I and Group II) were surgically obtained on days 5, 9, 13 and 15 and processed for histological examination.Results: The statistical analysis showed significant differences between irradiated and non-irradiated groups (P < 0.05). However, muscular degeneration was observed in 18% of the samples of Group I.Conclusion: It may be concluded that the LED therapy protocol established for this in vivo study was effective in reducing the severity of oral mucositis, although the oral lesions were not completely prevented. Lasers Surg. Med. 40:625-633, 2008. (c) 2008Wiley-Liss, Inc.
Keywords: drug therapy; fluorouracil; hamsters; neoplasms; oral mucosa; phototherapy